مقاربة التواصلية في تعليم اللغة العربية لأطفال بإستخدام اليوتوب: A communicative approach in teaching the Arabic language to children using YouTube - Zahriw, Zahroo; Mufidah, Nuril (Hasanuddin University, 2024)
Abstracts : This research is focused on the expansion of technology and communication in the digitalization era, which requires teachers to utilize these opportunities in teaching and learning activities to increase the effectiveness and efficiency of the learning process. YouTube is one of the social media that is loved by the public, so by using this media it is hoped that it will be able to increase students' attractiveness and ability in 4 skills of the Arabic language, namely listening, speaking, reading, and writing. The aim of this research is to describe 1) the meaning of a communicative approach 2) implementation of communicative approach in learning Arabic 3) implementation a communicative approach to learning Arabic in for children in elementary school using YouTube. The type of research used is qualitative descriptive research using the library search method. The data collection technique used is literature analysis from scientific journals, library studies and books. The results of this research show that 1) The communicative approach is an approach that focuses on students' communicative abilities, both in formal and non-formal environments. 2) The application of a communicative approach in Arabic can be based on active student learning, where students are the main object and the teacher is only a facilitator. 3) In its application students can practice their speaking skills by recording themselves and comparing them with videos of native speakers. Students can also improve their intonation and pronunciation by imitating the way native speakers speak. Creative videos can help students to develop their Arabic language skills and increase their interest in language learning. YouTube in audiovisual based Arabic language learning has been proven to be effective in increasing students' learning motivation, listening skills, vocabulary, speaking skills and creativity. Keyword : Arabic language learning, communicative approach and YouTube.